UJI FITOKIMIA DAN ANTIBAKTERI EKSTRAK METANOL DAUN MACARANGA LAMELLATA WHITMORE - Ramadhani, Riski Vebryanti; Marliana, Eva; Erwin, Erwin (Jurusan Kimia FMIPA UNMUL, 2019)
Phytochemical test and antibacterial activity of Macaranga lamellata Whitmore have been done. This research aims to find out the secondary metabolites using Thin Layer Chromatography (TLC) and to determine antibacterial activity by paper disc method from methanol extract on Macaranga lamellata Whitmore leaf. Based on the results obtained from phytochemical tests, it was known that methanol extract contains alkaloid, flavonoid, polyphenol and terpenoid/steroid compounds. Antibacterial activity obtained Minimum Inhibitory Concentration values from methanol extract for Streptococcus sobrinus KCCM 11898 and Salmonella typhi ATCC 422 at 0-0.5%.